Blockchain in Financial Services in Emerging Markets, Part I : Current Trends - Niforos, Marina (International Finance Corporation, Washington, DC, 2018)
Financial institutions around the world find themselves continually barraged by external innovations they are often unable to absorb and internalize. The emergence of innovative digital financial technologies has challenged traditional players in the sector by demonstrating new ways to deliver value across the entire financial value chain. Blockchain, or distributed ledger technology, is just such a disruptive, and possibly game-changing, innovation. Emerging markets are in general characterized by low banking penetration, the exit of financial players from certain markets, strong demand for financial inclusion both from individual consumers and small businesses, high levels of mobile penetration, and less developed business infrastructure and financial sector incumbents. These conditions in combination can be a powerful catalyst for the adoption of blockchain-based financial solutions and can provide the basis for a technological leap forward and a boost to financial inclusion and growth.